Occurrence of antibiotics in rural catchments. (February 2017) - Dinh, Quoc Tuc; Moreau-Guigon, Elodie; Labadie, Pierre; Alliot, Fabrice; Teil, Marie-Jeanne; Blanchard, Martine; Chevreuil, Marc
Abstract: The transfer of 23 antibiotics from domestic and hospital sources was investigated in two elementary river watersheds receiving wastewater treatment plant (WWTP) discharges, in relation with the hydrological cycle and seasonal conditions. Antibiotic concentrations in the effluent of a WWTP treating wastewaters from both hospital and domestic sources (18−12 850 ng L −1 ) were far higher than those from domestic sources exclusively (3–550 ng L −1 ). In rivers, upstream of the WWTP discharges, fluoroquinolones only were found at low concentrations (≤10 ng L −1 ). Their presence might be explained by transfer from contaminated agricultural fields located on the river banks. Immediately downstream of the WWTP discharge, antibiotic occurrence increased strongly with mean concentrations up to 1210 ng L −1 for ofloxacin and 100% detection frequencies for vancomycin, sulfamethoxazole, trimethoprim and three fluoroquinolones. Dilution processes during high-flow periods led to concentrations 14 times lower than during low-flow periods. Downstream of the discharge, the antibiotic dissipation rate from the water column was higher for fluoroquinolones, in relation with their high sorption upon suspended matter and sediment. Only five antibiotics (vancomycin and four fluoroquinolones ciprofloxacin, norfloxacin, ofloxacin and enoxacin) were partly distributed (11%–36%) in the particulate phase. Downstream of the discharge, antibiotic contents in sediment ranged from 1700 to 3500 ng g −1 dry weight, fluoroquinolones accounting for 97% of the total. Highlights: Among 23 antibiotics investigated, 15 occur in the mix hospital + domestic effluent. In rural watershed upstream of WWTP discharge, only fluoroquinolones occur. The discharge strongly impacts the river quality especially for the low flow period. Only fluoroquinolones are present in particulate phase in substantial quantity. Antibiotic distribution in the particulate phase controls their dissipation in river.